Effect of oral calcium carbonate on aortic calcification in apolipoprotein E-deficient (apoE-/-) mice with chronic renal failure - Phan, Olivier; Ivanovski, Ognen; Nikolov, Igor G; Joki, Nobuhiko; Maizel, Julien; Louvet, Loïc; Chasseraud, Maud; Nguyen-Khoa, Thao; Lacour, Bernard; Drüeke, Tilman B; Massy, Ziad A (Oxford University Press (OUP), 2008)
In chronic kidney disease (CKD) patients, the intake of calcium-based phosphate binders is associated with a marked progression of coronary artery and aortic calcification, in contrast to patients receiving calcium-free phosphate binders. The aim of this study was to reexamine the role of calcium carbonate in vascular calcification and to analyse its effect on aortic calcification-related gene expression in chronic renal failure (CRF).